Improving Aileron Effectiveness Based on Changing the Position of Aileron Connectors - Ju Qiu; Haisong Ang (International Journal of Aerospace Engineering)
In this paper, the design concept of the aileron with a fixed connector and a moving connector has been explored due to the improvement of aileron effectiveness. As usual, aileron reversal or the blocking phenomenon of multijoint fixed ailerons is a hard nut to crack. In the present research, in order to improve aileron effectiveness, several examples are studied. The connection position influences the stress, displacement, load distribution, and control effectiveness of the aileron or critical flutter speed. As the joint positions are different, the wing-aileron connection stiffness is also changing. The sample of the beam shows the weight reduction. The plate simulation indicates the decreased deformation and the better load distribution. The aileron trimming demonstrates the improvement of aileron effectiveness. And the flutter speed coupled with the aileron is different. All of these examples indicate the feasibility of this new concept of the aileron design, which means improving aileron effectiveness based on changing the position of aileron connectors. Finally, three different modes for wing-aileron connections are suggested for reference.